Structural brain abnormalities in adults with congenital heart disease: Prevalence and association with estimated intelligence quotient. (1st May 2020) - Kessler, Nora; Feldmann, Maria; Schlosser, Ladina; Rometsch, Sarah; Brugger, Peter; Kottke, Raimund; Knirsch, Walter; Oxenius, Angela; Greutmann, Matthias; Latal, Beatrice
Abstract: Background: Little is known about the prevalence of structural brain abnormalities and cognitive functioning in the growing population of patients with adult congenital heart disease (ACHD). Thus, our aim was to assess structural abnormalities on brain magnetic resonance imaging (MRI) and their association with intelligence quotient (IQ) in ACHD patients. Methods: Cross-sectional study in ACHD patients and healthy controls as comparison group. Brain MRI was performed on a 3 T MR scanner, and inspection of structural abnormalities was performed blinded to ACHD or control status. IQ was estimated using the vocabulary and matrix reasoning subtests from the Wechsler Adult Intelligence Scale, Fourth Edition. Results: A total number of 67 (55% males) ACHD patients and 55 (51% males) controls were included (mean age 26.9 and 26.0 years respectively). Abnormalities on brain MRI were detected in 29 of 46 (63%) ACHD patients and in none of the controls. Abnormalities consisted of focal infarction or atrophy, white matter lesions, microhemorrhages, and global atrophy. Mean estimated IQ was significantly lower in ACHD patients than in controls (98.51 versus 104.38; 95% CI: −10.09 to −1.66; P value = 0.007). Comparison between patients with and without cerebral abnormalities revealed no significant difference in estimated IQ. Conclusion: Our findings indicate a high prevalence and wide spectrum of structural brain abnormalities in ACHD patients. Furthermore, this population is at a higher risk of impaired intellectual functioning than healthy controls. However, the present study could not establish a statistically significant association between MRI findings and estimated IQ. Clinical trial registration: ClinicalTrials.gov ID: NCT04041557 ; URL: https://clinicaltrials.gov/ct2/show/NCT04041557?term=NCT04041557&rank=1 . Highlights: Adults with congenital heart disease frequently show structural brain abnormalities. Brain abnormalities are usually focal and small, and are not related to lower IQ. Cardiopulmonary bypass surgery is a risk factor for cerebral microhemorrhages.